1974
DOI: 10.1111/j.1399-3054.1974.tb03131.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Absorption, Translocation and Metabolism of Metribuzin [4‐amino‐6‐tert‐butyl‐3‐(methylthio)‐as‐triazine‐5(4H)one] by Soybean Cultivars

Abstract: Soybean {Glycine max (L.) Merr.) cultivars have been reported to range in tolerance to injury by 4-amino-6-tert-butyl-3-(methylthio)-a5-triazine-5(4H)one (metribuzin), from tolerant (e.g. 'Bragg') to susceptible (e.g. 'Coker 102' and 'Semmes'). 'Bragg', 'Coker 102', and 'Semmes' soybeans were grown in sand subirrigated with nutrient solution containing labelled (^^Ccarbonyl metribuzin) and nonlabelled metribuzin to determine cultivar variability in absorption, translocation, and metabolism of metribuzin. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
36
0
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 14 publications
2
36
0
1
Order By: Relevance
“…dimethylethyl)-3-(methylthio)-1,2,4-triazin-5(4H)-one] (4,14). Sweet corn, Zea mays L., cultivars have exhibited differential response to chloroacetamide and thiocarbamate herbicides (1).…”
mentioning
confidence: 99%
“…dimethylethyl)-3-(methylthio)-1,2,4-triazin-5(4H)-one] (4,14). Sweet corn, Zea mays L., cultivars have exhibited differential response to chloroacetamide and thiocarbamate herbicides (1).…”
mentioning
confidence: 99%
“…For personal use only. Smith and Wilkinson (1974) and Stephanson et al (1976) (five-leaf) in the early morning under conditions of bright sunlight, low RH, warm air temperatures, drier soil moisture levels and lower rares of the herbicide (0.14-0.21 kg/ha).…”
mentioning
confidence: 99%
“…The extraction procedure was similar to the one used by Smith and Wilkinson (1974 (Table l). However, Fedtke (1972) showed that 0.3-1.0 ppm metribuzin increased the total dry matter production of potatoes because it lowered the daytime respiration rate.…”
mentioning
confidence: 99%
“…The absorption and metabolism of C1a-metribuzin l4-arnino-6-terr-butyl- Smith and Wilkinson (1974) and for tomatoes by Stephenson et al (1976). Hargroder and Rogers (1974) peated using a second set of plants.…”
mentioning
confidence: 99%